Regulation of Alternative Splicing by Reversible Protein Phosphorylation - Stamm, Stefan (The Journal of biological chemistry, 2008)
The vast majority of human protein-coding genes are subject to alternative splicing, which allows the generation of more than one protein isoform from a single gene. Cells can change alternative splicing patterns in response to a signal, which creates protein variants with different biological properties. The selection of alternative splice sites is governed by the dynamic formation of protein complexes on the processed pre-mRNA. A unique set of these splicing regulatory proteins assembles on different pre-mRNAs, generating a “splicing” or “messenger ribonucleoprotein code” that determines exon recognition. By influencing protein/protein and protein/RNA interactions, reversible protein phosphorylation modulates the assembly of regulatory proteins on pre-mRNA and therefore contributes to the splicing code. Studies of the serine/arginine-rich protein class of regulators identified different kinases and protein phosphatase 1 as the molecules that control reversible phosphorylation, which controls not only splice site selection, but also the localization of serine/arginine-rich proteins and mRNA export. The involvement of protein phosphatase 1 explains why second messengers like cAMP and ceramide that control the activity of this phosphatase influence alternative splicing. The emerging mechanistic links between splicing regulatory proteins and known signal transduction pathways now allow in detail the understanding how cellular signals modulate gene expression by influencing alternative splicing. This knowledge can be applied to human diseases that are caused by the selection of wrong splice sites.